Teleradiology in the operating room of the future...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Farahani K; Valentino DJ; Ratib O (Journal of Digital Imaging)
Recent advances in magnetic resonance imaging (MRI) are rapidly making this modality the imaging method of choice for image-guided neurosurgical operations. However, to be ready for its prime time in the operating room (OR), utilization of MRI in the OR requires development of better techniques for image-guided navigation, as well as interactive real-time teleradiologic methods that will allow tele-collaboration between the surgeon and the radiologist. This presentation describes our work in progress toward achievement of teleradiology in the OR. Copyright (c) 1999 by W.B. Saunders Company